Telehealth Education in Athletic Training - W. David Carr; McCall Christian; Jennifer Volberding; Zachary Winkelmann (Bowling Green State University, 2024)
Context: Within the broad telehealth education literature, there are numerous case studies and position statements from various associations of model practices. Little is known about how athletic training is addressing telehealth education. Objective: To determine how athletic training education programs teach, assess, and structure telehealth content. Design: Cross-sectional study Setting: Online survey instrument Patients or Other Participants: An institutional athletic training faculty member from 82 athletic training programs in the United States. Data Collection and Analysis: The survey contained the validated Telehealth Evaluative Content in Higher Education (TECHE) instrument, which consisted of descriptive items focused on how education programs teach, assess, and deliver telehealth education content. Data were cleaned and basic descriptive statistics were calculated. Results: Of the program faculty that responded, 49% (n=39) reported that their program includes telehealth content. Specifically, 19 programs (49%) taught about the knowledge, skills, and abilities using multiple presentations across the curriculum (42%, n = 8) ,including techniques such as class discussions (68%, n = 13) and lectures (63%, n = 12). For assessment, 17 programs (44%) included simulations (65%, n = 11) evaluated most commonly by faculty (82%, n = 14). Only 14 (36%) programs created telehealth clinical experiences including practice with simulated patients throughout all the domains of telehealth skills. When programs included telehealth clinical experiences, they mainly focused (28%, n = 16) on orthopedics and (26%, n = 15) on primary care experiences. Discussion: The development of telehealth content should be based on model practices and delivered across multiple curriculum presentations. Assessment should incorporate various perspectives and utilize different methods. Practice opportunities with classmates and simulated patients that require interpersonal communication, data gathering, and patient education should be developed. Conclusion: While a slight majority of programs do not teach telehealth content, those that do teach telehealth utilize various strategies. Most program faculty use simulations conducted by faculty to assess orthopedic and primary care telehealth content.